2019
DOI: 10.5121/ijcsit.2019.11407
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum Occupancy in Rural Nigeria: A Case for A Lightly Licensed Spectrum Band for Rural Broadband Enhancement

Abstract: A detailed report of the spectrum occupancy measurement drive conducted outdoors in three rural villages of Asong in Mkpat Enin, Ikot Akpabio in Etinan, and Afaha Offioing in Nsit Ibom Local Government Areas of Akwa Ibom state in Nigeria on the UHF and VHF broadcast frequency bands is here presented. The spectrum usage on a highly conservative noise floor, was high in the VHF band, thereby not having enough free bandwidth for secondary spectrum access while the UHF band percentage utilization for the three vil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A research study conducted in [23], in Nigeria found that there is a need for more bandwidth for secondary rural broadband service providers due to high VHF band spectrum utilization in three villages. The UHF band usage was 33%, 41%, and 55% in Asong, Ikot Akpabio, and Afaha-Offiong, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A research study conducted in [23], in Nigeria found that there is a need for more bandwidth for secondary rural broadband service providers due to high VHF band spectrum utilization in three villages. The UHF band usage was 33%, 41%, and 55% in Asong, Ikot Akpabio, and Afaha-Offiong, respectively.…”
Section: Introductionmentioning
confidence: 99%